Modeling and simulation of sodium sulfur battery for battery energy storage system and custom power devices - Chung L.W.; Siam M.F.M.; Ismail A.B.; Hussien Z.F. (2023)
This paper presents an overview of Sodium-Sulfur NAS battery used for Battery Energy Storage System and custom power devices for power quality applications. Several electrical battery models are reviewed and discussed. Using one of the most accurate electrical battery models, the voltage-current behavior and characteristics of NAS battery are modeled and simulated using EMTDC/PSCAD software tool. Comparison between simulation and experimental results are presented for a 50kW battery model to validate the simulation model and to analyze NAS battery output performance with respect to battery's depth of discharge and temperature change. 2004 IEEE.